AB0002 Effect of common polymorphisms in the methotrexate pharmacokinetic pathway on efficacy/adverse effects and methotrexate polyglutamate levels in ra. (12th June 2018) - Sandhu, A.; Dhir, V.; Ahmed, S.
Abstract : Background: Measurement of erythrocyte methotrexate polyglutamate levels (MTX-glun ) are widely used to predict response and adverse effects to methotrexate in rheumatoid arthritis patients, but there are very few studies in which these levels were correlated with common polymorphisms in genes involved in methotrexate (MTX) pharmacokinetics. This preliminary study evaluated their utility in Asian Indian patients in a prospective study over 24 weeks. Objectives: The objective of this study is to investigate the impact of seven common polymorphisms in genes involved in methotrexate (MTX) pharmacokinetics on response, adverse effects and methotrexate polyglutamate (MTXPG) levels in rheumatoid arthritis. Methods: This study enrolled 117 RA patients who were treated prospectively with MTX for 24 weeks. Patients were categorised on the EULAR criteria into responders (good and moderate) and non-responders. Adverse effects were ascertained using a questionnaire. The following polymorphisms were ascertained using hyrolysis probes – rs1045642 (ABCB1 3435C>T), rs1128503 (ABCB1 1236C>T), rs10106 (FPGS 1994A>G), rs1544105 (FPGS G>A), rs11545078 (GGH 452C>T), rs3758149 (GGH −401C>T) and rs1051266 (RFC1 80G>A). RBC MTXPG1–5 levels were determined using HPLC at 4, 8, 16 and 24 weeks. Results: There was a significant association of the GGH 452C>T CC genotype (OR 9.5, 95% CI 1.2 to 76.0) with response to MTX. On logistic regression, higher DAS28 3 at baseline and GGH 452CC genotype were significantly associated with response (table 1); the accuracy of the model was 75%. The FPGS 1994A>G GG genotype was associated with a significantly lower risk of adverse effects to MTX (Odds Ratio 0.3 (95% CI 0.1 to 0.6)). On logistic regression, FPGS 1994GG genotype and lower BMI were significant predictors for adverse effects with an accuracy of 66%. The other polymorphisms were not associated with response or adverse effects. None of the polymorphisms were associated with change in MTXPG levels. Conclusions: GGH 452 CC genotype was found to be associated with response to MTX and FPGS 1994 A>G GG with a lower risk of adverse effects; however, not by change in MTXPG levels. References: [1] Stamp LK, Chapman PT, O'Donnell JL, Zhang M, James J, Frampton C, Barclay ML, Kennedy MA, Roberts RL. Polymorphisms within the folate pathway predict folate concentrations but are not associated with disease activity in rheumatoid arthritis patients on methotrexate. Pharmacogenet Genomics2010Jun;20(6):367–76. doi:10.1097/FPC.0b013e3283398a71. PubMed PMID: 20386493. [2] Dervieux T, Greenstein N, Kremer J. Pharmacogenomic and metabolic biomarkers in the folate pathway and their association with methotrexate effects during dosage escalation in rheumatoid arthritis. Arthritis Rheum2006Oct;54(10):3095–103. PubMed PMID: 17009228. [3] Sandhu A, Dhir V, Bhatnagar A, Dhawan V, Kaur J, Sood A, Naidu S, Ahmad S, Varma N, Sharma A, Sharma S. High Methotrexate Triglutamate Level Is an Independent Predictor of Adverse Effects in Asian Indian Rheumatoid Arthritis Patients-A Preliminary Study. Ther Drug Monit. 2017Apr;39(2):157–163. doi:10.1097/FTD.0000000000000375 [PubMed PMID: 28107255]. Acknowledgements: ICMR New Delhi: For Amit Sandhu Fellowship APLAR: For Funding this project Disclosure of Interest: None declared